Impact of the American Society of Colon and Rectal Surgeons' Research Foundation Grants on Academic Colorectal Surgeons' Career Trajectory. Issue 2 (February 2019) - Kaplan, Jennifer A.; Hedrick, Traci L.; Kalady, Matthew F.; Shaffer, Virginia O.; Flemming, Fergal J.; Wick, Elizabeth C.
Abstract : Supplemental Digital Content is available in the text.